Analysis of geometrical layout of tram tracks based on the railway methods - Szmagliński, Jacek (Przegląd Komunikacyjny)
The paper describes problems occurring during travelling by trams over curves. It was determined that stong jerks occur as a result of the lack of analysis of kinematic parameters on curves and changes in the construction scheme of trams. A proposal for a computational methodology has been given. Calculations of kinematic parameters were carried out for typical geometric layouts in accordance with the Polish Guidelines.